Impact of Inflation on Per Capita Income in Emerging Economies: Evidence from BRICS Nations - Chisti, Khalid Ashraf; Ali, Khursheed; Sangmi, Mohi-ud-din (Journal of Empirical Studies, 2015)
In this paper an attempt has been made to analyse the impact of Inflation on per capita income of emerging economies. In order to achieve the objective of the study the researchers have taken five major emerging countries of the world which are the members of BRICS. For the purpose of analysis the data related to thirteen years have been taken from 1999 to 20011. After employing the regression model, the results confirm that independent variable (inflation) do not statistically influence the dependent variable (Per Capita Income) in the three countries which are India, Brazil and South Africa. However, in the other two countries (China and Russia) the findings affirm the independent variable (Inflation) do statistically influence the dependent variable (Per Capita Income).Therefore, it can be concluded that a change in the inflation can not necessarily bring a change in the per capita income of the country.